Characteristics of Phyllosphere Microbial Communities Associated with Three Different Plants in the Semi-arid Areas of Northwest Liaoning - Keye Zhu; Wenxu Zhu; Weixi Zhang; Jiaying Liu; Changjun Ding (Journal of Soil Science and Plant Nutrition, 2023)

Characterization of ectomycorrhizal fungal communities associated with tree species on an iron tailings deposit undergoing restoration - Wenxu Zhu; Changjun Ding; Keye Zhu; Weixi Zhang; Dejun Liang; XiaoJiang Wang; Aiping Li; Xiaohua Su (Environmental Science and Pollution Research, 2022)
Vegetation restoration is an effective method to improve the ecological environment of mine tailings, which has a profound impact on the potential ecological functions of soil fungal communities; yet, little is known about its beneficial effect on soil ectomycorrhizal fungal community. In this study, the responses of soil characteristics and soil ectomycorrhizal fungal community diversity and structure to different revegetation, as well as the contribution of soil factors to soil ectomycorrhizal community were investigated in Liaoning Province, China. As we anticipated, the presence of vegetation significantly improved most soil properties we studied. What’s more, compared to Korean pine ( Pinus koraiensis Sieb. et Zucc.), Chinese poplar ( Populus simonii Carr), and black locust ( Robinia pseudoacacia L) could better improve soil total carbon, total nitrogen, total phosphorus, and available phosphorus. In addition, soil ectomycorrhizal fungal community diversity in black locust was greater than Korean pine and Populus simonii . Nonmetric multidimensional scaling analyses indicated that soil ectomycorrhizal community significantly differed depending on different revegetation types. Thus, these results indicated that black locust could be a suitable species for the revegetation of iron mine tailings. The study provided theoretical basis for ecological restoration of iron mine tailings using local plant species.